A preparation method and system of high dielectric composite LTCC material

By doping LiNb0.6Ti0.34 (Cu1/3Nb2/3)0.16O3 and LiBa3Nb3Ti5O21 two-phase composite materials with LiF flux, the existing high-dielectric constant LTCC materials are solved, and a high-dielectric composite LTCC material with high dielectric constant, low loss and excellent temperature coefficient is achieved.

CN118724589BActive Publication Date: 2025-02-28YANGTZE DELTA REGION INST OF UNIV OF ELECTRONICS SCI & TECH OF CHINE (HUZHOU)
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411216285.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-02
Publication Date
2025-02-28
Estimated Expiration
2044-09-02

AI Technical Summary

Technical Problem

The existing LTCC materials with high dielectric constants are not large in application, have high losses and poor temperature coefficient characteristics, resulting in few related research reports.

Method used

LiNb0.6Ti0.34 (Cu1/3Nb2/3)0.16O3 and LiBa3Nb3Ti5O21 are used, and a small amount of LiF is added to fuse. Through appropriate proportions of composite and flux doping, the sintering temperature is reduced to 900°C, while maintaining high dielectric constant and low dielectric loss.

Benefits of technology

A high-dimension composite LTCC material with a dielectric constant of more than 65, a dielectric loss of less than 8500, and a resonant frequency temperature coefficient is nearly zero, which combines low-temperature sintering and excellent electrical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The present invention belongs to the technical field of electronic functional ceramic materials and their manufacturing, and discloses a method and system for preparing a high dielectric composite LTCC material. The high dielectric low loss LTCC material provided by the present invention adopts an appropriate amount of LiNb 0.6 Ti 0.34 (Cu 1 / 3 Nb 2 / 3 ) 0.16 O3 and LiBa3Nb3Ti5O 21 The LiNbO2 is composited and doped with a small amount of LiF which also contains Li ions. 0.6 Ti 0.34 (Cu 1 / 3 Nb 2 / 3 ) 0.16 O3 and LiBa3Nb3Ti5O 21 Both materials have the characteristics of high dielectric constant and low loss. The former has a negative resonant frequency temperature coefficient, and the latter has a positive resonant frequency temperature coefficient. The two pre-sintered materials are compounded in an appropriate proportion. If no other phase is produced during the compounding process, the resonant frequency temperature coefficient can be adjusted to zero, and a high dielectric constant and Qf value can still be maintained. At the same time, a small amount of LiF containing Li ions is used for fluxing. Studies have found that this flux has good tolerance for the composite material system in the present invention, and can effectively reduce the sintering temperature of the material system to 900°C without significant effect on its electrical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electronic functional ceramic materials and their manufacturing, and in particular relates to a preparation method and system of a high dielectric constant composite LTCC material. Background Art

[0002] LTCC (low temperature co-fired ceramic) technology is the most mainstream passive integration technology at present, and it has played a very important role in realizing the miniaturization and integration of electronic components. At present, microwave devices widely used in the microwave and radio frequency fields, including filters, power dividers, baluns, antennas, etc., all need to use LTCC technology to achieve chip-type and miniaturization. LTCC materials can be divided into three categories: low dielectric, medium dielectric and high dielectric. Generally, LTCC materials with a dielectric constant lower than 10 belong to low dielectric LTCC materials, which are also the most studied LTCC materials reported at present, including a variety of silicates, phosphates, borates, and materials composed of microcrystalline glass and glass + ceramics. It can not only prepare various LTCC microwave devices, but also can be used in LTCC substrates. LTCC materials with a dielectric constant between 10 and 50 belong to medium LTCC materials, which are generally suitable for preparing various LTCC microwave devices. Compared with microwave devices prepared with low dielectric LTCC materials, they have obvious advantages in reducing the volume and size of devices. LTCC materials with a dielectric constant exceeding 50 can generally be classified as high-dielectric LTCC materials, which have obvious advantages in reducing the size and volume of LTCC microwave devices with lower application frequency bands. Because the characteristic size of a microwave device is inversely proportional to its operating frequency, the lower the operating frequency, the larger the corresponding device size, so it is necessary to use materials with higher dielectric constants to achieve its miniaturization. However, since the current application of high-dielectric-constant LTCC materials is not very large, and its loss is higher than that of medium- and low-dielectric LTCC materials, and its temperature coefficient characteristics are also poor, there are not many related research reports.

[0003] Through the above analysis, the problems and defects of the prior art are as follows:

[0004] Since the application volume of high dielectric constant LTCC materials is not very large at present, and their loss is higher and the temperature coefficient characteristics are worse than those of medium and low dielectric constant LTCC materials, there are not many related research reports. Summary of the invention

[0005] In view of the problems existing in the prior art, the present invention provides a method for preparing a high dielectric constant composite LTCC material.

[0006] The present invention is achieved by: a method for preparing a high dielectric composite LTCC material comprising:

[0007] Step 1, preparation of LiNb 0.6 Ti 0.34(Cu 1 / 3 Nb 2 / 3 ) 0.16 O3 pre-burned material.

[0008] Step 2, preparation of LiBa3Nb3Ti5O 21 Pre-burned material.

[0009] Step 3: Combine Step 1 and Step 2 to obtain LiNb 0.6 Ti 0.34 (Cu 1 / 3 Nb 2 / 3 ) 0.16 O3 and LiBa3Nb3Ti5O 21 Pre-burned material, according to x%LiNb 0.6 Ti 0.34 (Cu 1 / 3 Nb 2 / 3 ) 0.16 O3+(100-x)%LiBa3Nb3Ti5O 21 +y%LiF, wherein 65≤x≤70, 0.75≤y≤1, is weighed and mixed, and then deionized water and ball milling medium are added in a mass ratio of 1:2:5, and the ball milling is performed at a ball milling speed of 300rpm for 8h. After ball milling, the powder is dried at 120°C for use.

[0010] Step 4, adding 20wt% of PVA solution (concentration 8wt%) as a binder to the dried powder obtained in step 3, granulating and uniaxial dry pressing.

[0011] Step 5, placing the product obtained in step 4 into a sintering furnace, heating the temperature to 200°C at a heating rate of 2°C / min and keeping it for 2 hours to drain water, then heating the temperature to 500°C to drain the binder for 3 hours, then heating the temperature to 900°C at a heating rate of 3°C / min and keeping it for 3 hours, cooling it to room temperature with the furnace to obtain a test sample.

[0012] Furthermore, the preparation of LiNb 0.6 Ti 0.34 (Cu 1 / 3 Nb 2 / 3 ) 0.16 O3 pre-burning material method.

[0013] Analytical pure Li2CO3, Nb2O5, TiO2, CuO were mixed according to LiNb 0.6 Ti 0.34 (Cu 1 / 3 Nb 2 / 3 ) 0.16 The ingredients are prepared according to the molar ratio of each cation in the O3 molecular formula.

[0014] Then, the mixture was ball-milled once to make the ingredients uniformly mixed, and deionized water and ball-milling medium were added in a mass ratio of 1:2:5. The mixture was ball-milled for 4 h at a planetary ball mill speed of 300 rpm. After ball-milling, the obtained powder was dried at 120°C. The dried powder was passed through a 40-mesh sieve, sieved, and then placed in a crucible for compaction. The powder was pre-sintered at a heating rate of 3°C / min to 850°C, kept warm for 4 h, and cooled with the furnace to obtain LiNb 0.6 Ti 0.34 (Cu 1 / 3 Nb 2 / 3 ) 0.16 O3 pre-burned material.

[0015] Further, the preparation of LiBa3Nb3Ti5O 21 Pre-burned material.

[0016] Analytical pure Li2CO3, BaCO3, Nb2O5, TiO2, LiBa3Nb3Ti5O 21 The ingredients are prepared according to the molar ratio of each cation in the molecular formula; then they are ball-milled once to make the ingredients evenly mixed, and deionized water and ball-milling medium are added according to the mass ratio of 1:2:5 of the ingredients, and the ball mill is carried out at a planetary ball mill speed of 300 rpm for 4 hours. After ball milling, the obtained powder is dried at 120°C.

[0017] The dried powder was passed through a 40-mesh sieve, sieved, placed in a crucible, compacted, and pre-sintered at a heating rate of 3°C / min to 880°C, kept at that temperature for 4 hours, and cooled in the furnace to obtain LiBa3Nb3Ti5O 21 Pre-burned material.

[0018] Another object of the present invention is to provide a system for preparing a high dielectric constant composite LTCC material, comprising:

[0019] Preparation of pre-sintered materials for preparing LiNb 0.6 Ti 0.34 (Cu 1 / 3 Nb 2 / 3 ) 0.16 O3 pre-sintered material; preparation of LiBa3Nb3Ti5O 21 Pre-burned material.

[0020] Ratio of pre-sintered materials to obtain LiNb 0.6 Ti 0.34 (Cu 1 / 3 Nb 2 / 3 ) 0.16 O3 and LiBa3Nb3Ti5O 21 Pre-burned material, according to x%LiNb 0.6 Ti 0.34 (Cu1 / 3 Nb 2 / 3 ) 0.16 O3+(100-x)%LiBa3Nb3Ti5O 21 +y%LiF, where 65≤x≤70, 0.75≤y≤1, is weighed and mixed.

[0021] Ball milling and drying of pre-sintered materials: adding deionized water and ball milling medium in a mass ratio of 1:2:5 according to the ingredients, ball milling at a speed of 300 rpm for 8 hours, and drying the powder at 120°C for later use.

[0022] The dry pressed powder is used to add 20wt% of the obtained dried powder into a PVA solution (concentration 8wt%) as a binder, granulate it and perform uniaxial dry pressing.

[0023] The sintering material is used to put the obtained product into a sintering furnace, and the temperature is first increased to 200°C at a heating rate of 2°C / min and kept for 2 hours to drain water, then increased to 500°C to drain the binder for 3 hours, and then increased to 900°C at a rate of 3°C / min and kept for 3 hours, and cooled to room temperature with the furnace to obtain a test sample.

[0024] In combination with the above technical solutions and the technical problems solved, please analyze the advantages and positive effects of the technical solutions to be protected by the present invention from the following aspects:

[0025] First, the present invention proposes a method for preparing a high dielectric constant and low loss LTCC material with a dielectric constant exceeding 65. 0.6 Ti 0.34 (Cu 1 / 3 Nb 2 / 3 ) 0.16 O3 and LiBa3Nb3Ti5O 21 The two-phase composite is then doped with a small amount of LiF flux. Our previous research has shown that LiNb can be replaced by an appropriate amount of Cu and Nb ions. 0.6 Ti 0.34 (Cu1 / 3Nb2 / 3) 0.16 O3 ceramics can not only maintain a high dielectric constant (about 65), but also reduce the sintering temperature to 950℃, and can obtain low dielectric loss (Qf value is about 9000). However, its resonant frequency temperature coefficient is still 24ppm / ℃, and it also cannot meet the low temperature sintering conditions of 900℃ or below required by the LTCC process. Therefore, we mixed the pre-sintered material of this material with LiBa3Nb3Ti5O 21The materials are composited in two phases, and an appropriate amount of LiF dopant is added to assist fluxing, reducing the sintering temperature of the material system to about 900°C. The study found that the two materials will not produce new phases after composite, and can not only maintain a high dielectric constant and high Qf value (ε r ﹥65, Qf﹥8500), and the resonant frequency temperature coefficient of the composite material can also be adjusted to near zero (τ f =6~+6ppm / ℃), so it is a high dielectric LTCC material with excellent comprehensive effects.

[0026] The high dielectric constant and low loss LTCC material provided by the present invention adopts an appropriate amount of LiNb 0.6 Ti 0.34 (Cu 1 / 3 Nb 2 / 3 ) 0.16 O3 and LiBa3Nb3Ti5O 21 The LiNbO2 is composited and doped with a small amount of LiF which also contains Li ions. 0.6 Ti 0.34 (Cu 1 / 3 Nb 2 / 3 ) 0.16 O3 and LiBa3Nb3Ti5O 21 Both materials have the characteristics of high dielectric constant and low loss. The former has a negative resonant frequency temperature coefficient, and the latter has a positive resonant frequency temperature coefficient. The two pre-sintered materials are compounded in an appropriate proportion. If no other phases are produced during the compounding process, the resonant frequency temperature coefficient can be adjusted to zero, and the high dielectric constant and Qf value can still be maintained. At the same time, a small amount of LiF, which also contains Li ions, is used for fluxing. Studies have found that this flux has good tolerance for the composite material system in the present invention, and can effectively reduce the sintering temperature of the material system to 900°C with almost no significant effect on its electrical properties. The high dielectric composite LTCC material finally obtained has both low temperature sintering (900°C sintering), high dielectric constant (ε r ﹥65), low dielectric loss (Qf﹥8500) and near-zero resonant frequency temperature coefficient (τ f =6~+6ppm / ℃) and other advantages. Through XRD detection, it was found that this LTCC material also only contains Li 1.075 Nb 0.625 Ti 0.45 O3 (with LiNb 0.6 Ti 0.34 (Cu 1 / 3 Nb 2 / 3 ) 0.16 O3 crystal structure) and LiBa3Nb3Ti50 21 Two-phase structure.

[0027] Second, whether the technical solution of the present invention solves the technical problems that people have always been eager to solve but have never been able to solve successfully.

[0028] The technical solution of the present invention well realizes a high dielectric constant (ε r ﹥65) LTCC materials have very significant value and significance in reducing the size of LTCC integrated devices with relatively low operating frequencies (the lower the operating frequency, the larger the size of the LTCC device) and those designed and processed based on SIW (integrated waveguide) structures. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 It is a flow chart of a method for preparing a high dielectric composite LTCC material provided by an embodiment of the present invention.

[0030] Figure 2 It is a process flow chart of the preparation of the high dielectric composite LTCC material provided by an embodiment of the present invention.

[0031] Figure 3 This is an XRD diagram of the high dielectric constant composite LTCC material provided by an embodiment of the present invention. DETAILED DESCRIPTION

[0032] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0033] like Figure 1 As shown, a method for preparing a high dielectric composite LTCC material provided by an embodiment of the present invention comprises the following steps:

[0034] S101, preparation of LiNb 0.6 Ti 0.34 (Cu 1 / 3 Nb 2 / 3 ) 0.16 O3 pre-burned material.

[0035] S102, preparation of LiBa3Nb3Ti5O 21 Pre-burned material.

[0036] S103, S101 and S102 to obtain LiNb 0.6 Ti 0.34 (Cu 1 / 3 Nb 2 / 3 ) 0.16 O3 and LiBa3Nb3Ti5O 21 Pre-burned material, according to x%LiNb 0.6 Ti 0.34 (Cu1 / 3 Nb 2 / 3 ) 0.16 O3+(100-x)%LiBa3Nb3Ti5O 21 +y%LiF, wherein 65≤x≤70, 0.75≤y≤1, is weighed and mixed, and then deionized water and ball milling medium are added in a mass ratio of 1:2:5, and the ball milling is performed at a ball milling speed of 300rpm for 8h. After ball milling, the powder is dried at 120°C for use.

[0037] S104, adding 20 wt% of PVA solution (concentration 8 wt%) as a binder to the dried powder obtained in S103, granulating the powder and performing uniaxial dry pressing.

[0038] S105, put the product obtained from S104 into a sintering furnace, heat it to 200°C at a heating rate of 2°C / min, keep it at that temperature for 2 hours to drain water, then heat it to 500°C to drain the binder for 3 hours, then heat it to 900°C at a rate of 3°C / min and keep it at that temperature for 3 hours, cool it to room temperature with the furnace, and obtain the test sample.

[0039] Preparation of LiNb provided by the embodiment of the present invention 0.6 Ti 0.34 (Cu 1 / 3 Nb 2 / 3 ) 0.16 O3 pre-burning material method.

[0040] Analytical pure Li2CO3, Nb2O5, TiO2, CuO were mixed according to LiNb 0.6 Ti 0.34 (Cu 1 / 3 Nb 2 / 3 ) 0.16 The ingredients are prepared according to the molar ratio of each cation in the O3 molecular formula.

[0041] Then, the mixture was ball-milled once to make the ingredients uniformly mixed, and deionized water and ball-milling medium were added in a mass ratio of 1:2:5. The mixture was ball-milled for 4 h at a planetary ball mill speed of 300 rpm. After ball-milling, the obtained powder was dried at 120°C. The dried powder was passed through a 40-mesh sieve, sieved, and then placed in a crucible for compaction. The powder was pre-sintered at a heating rate of 3°C / min to 850°C, kept warm for 4 h, and cooled with the furnace to obtain LiNb 0.6 Ti 0.34 (Cu 1 / 3 Nb 2 / 3 ) 0.16 O3 pre-burned material.

[0042] Preparation of LiBa3Nb3Ti5O provided in the embodiment of the present invention 21 Pre-burned material.

[0043] Analytical pure Li2CO3, BaCO3, Nb2O5, TiO2, LiBa3Nb3Ti5O 21 The ingredients are prepared according to the molar ratio of each cation in the molecular formula; then they are ball-milled once to make the ingredients evenly mixed, and deionized water and ball-milling medium are added according to the mass ratio of 1:2:5 of the ingredients, and the ball mill is carried out at a planetary ball mill speed of 300 rpm for 4 hours. After ball milling, the obtained powder is dried at 120°C.

[0044] The dried powder was passed through a 40-mesh sieve, sieved, placed in a crucible, compacted, and pre-sintered at a heating rate of 3°C / min to 880°C, kept at that temperature for 4 hours, and cooled in the furnace to obtain LiBa3Nb3Ti5O 21 Pre-burned material.

[0045] It should be noted that:

[0046] There is no order of precedence between S101 and S102 described above.

[0047] If tape casting materials are needed for the development of LTCC devices, the powder prepared by S103 can be dried through a 60-120 mesh sieve before the LTCC tape casting slurry is prepared, and then the subsequent green embryo film preparation can be carried out.

[0048] A system for preparing a high dielectric constant composite LTCC material provided by an embodiment of the present invention comprises:

[0049] Preparation of pre-sintered materials for preparing LiNb 0.6 Ti 0.34 (Cu 1 / 3 Nb 2 / 3 ) 0.16 O3 pre-sintered material; preparation of LiBa3Nb3Ti5O 21 Pre-burned material.

[0050] Ratio of pre-sintered materials to obtain LiNb 0.6 Ti 0.34 (Cu 1 / 3 Nb 2 / 3 ) 0.16 O3 and LiBa3Nb3Ti5O 21 Pre-burned material, according to x%LiNb 0.6 Ti 0.34 (Cu 1 / 3 Nb 2 / 3 ) 0.16 O3+(100-x)%LiBa3Nb3Ti5O 21 +y%LiF, where 65≤x≤70, 0.75≤y≤1, is weighed and mixed.

[0051] Ball milling and drying of pre-sintered materials: adding deionized water and ball milling medium in a mass ratio of 1:2:5 according to the ingredients, ball milling at a speed of 300 rpm for 8 hours, and drying the powder at 120°C for later use.

[0052] The dry pressed material is used to add 20wt% of the obtained dried powder into a PVA solution (concentration 8wt%) as a binder, granulate it and perform uniaxial dry pressing molding.

[0053] The sintering material is used to put the obtained product into a sintering furnace, and the temperature is first increased to 200°C at a heating rate of 2°C / min and kept for 2 hours to drain water, then increased to 500°C to drain the binder for 3 hours, and then increased to 900°C at a rate of 3°C / min and kept for 3 hours, and cooled to room temperature with the furnace to obtain a test sample.

[0054] Figure 2 It is a process flow chart of the preparation of the high dielectric composite LTCC material provided by an embodiment of the present invention.

[0055] Figure 3 This is an XRD diagram of the high dielectric constant composite LTCC material provided by an embodiment of the present invention.

[0056] Table 1 Comprehensive dielectric properties of composite high-k LTCC materials sintered at 900℃ with different x and y values

[0057]

[0058] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Any modifications, equivalent substitutions and improvements made by any technician familiar with the technical field within the technical scope disclosed by the present invention and within the spirit and principle of the present invention should be covered by the protection scope of the present invention.

Claims

1. A method for preparing a high dielectric constant composite LTCC material, characterized in that: The following steps are involved: Step 1. Preparation of LiNb 0.6 Ti 0.34 (Cu 1 / 3 Nb 2 / 3 ) 0.16 O3 pre-burned material; Step 2. Preparation of LiBa3Nb3Ti5O 21 Pre-burned materials; Step 3. LiNb obtained in Step 1 and Step 2 0.6 Ti 0.34 (Cu 1 / 3 Nb 2 / 3 ) 0.16 O3 and LiBa3Nb3Ti5O 21 Pre-burned material, according to x%LiNb 0.6 Ti 0.34 (Cu 1 / 3 Nb 2 / 3 ) 0.16 O3+(100-x)%LiBa3Nb3Ti5O 21 +y%LiF, wherein 65≤x≤70, 0.75≤y≤1, is weighed and mixed, and then deionized water and ball milling medium are added according to the weight ratio of 1:2:5, and the ball milling is performed at a ball milling speed of 300 rpm for 8 hours. After the ball milling, the powder is dried at 120°C for use; Step 4. Add 20wt% of PVA solution as a binder to the dried powder obtained in step 3, granulate it and perform uniaxial dry pressing, wherein the concentration of the PVA solution is 8wt%; Step 5. Place the product obtained in step 4 into a sintering furnace, heat it to 200°C at a heating rate of 2°C / min and keep it for 2 hours to drain water, then heat it to 500°C to drain the binder for 3 hours, then heat it to 900°C at a heating rate of 3°C / min and keep it for 3 hours, cool it to room temperature with the furnace, and obtain a test sample.

2. The method for preparing a high dielectric constant composite LTCC material according to claim 1, characterized in that: The preparation of LiNb 0.6 Ti 0.34 (Cu 1 / 3 Nb 2 / 3 ) 0.16 The method of pre-firing O3 material includes: Analytical pure Li2CO3, Nb2O5, TiO2, CuO were mixed according to LiNb 0.6 Ti 0.34 (Cu 1 / 3 Nb 2 / 3 ) 0.16 The ingredients are prepared according to the molar ratio of each cation in the O3 molecular formula; Then, the mixture was ball-milled once to make the ingredients uniformly mixed, and deionized water and ball-milling medium were added in a mass ratio of 1:2:5, and the mixture was ball-milled for 4 hours at a speed of 300 rpm in a planetary ball mill. After ball-milling, the obtained powder was dried at 120°C; The dried powder was passed through a 40-mesh sieve, sieved, placed in a crucible, compacted, and pre-sintered at a heating rate of 3°C / min to 850°C, kept at that temperature for 4 hours, and cooled in the furnace to obtain LiNb 0.6 Ti 0.34 (Cu 1 / 3 Nb 2 / 3 ) 0.16 O3 pre-burned material.

3. The method for preparing a high dielectric constant composite LTCC material according to claim 1, characterized in that: The preparation of LiBa3Nb3Ti5O 21 Methods for pre-firing materials include: Analytically pure Li2CO3, BaCO3, Nb2O5, and TiO2 were prepared according to the formula of LiBa3Nb3Ti5O 21 The ingredients are prepared according to the molar ratio of each cation in the molecular formula; Then, the mixture was ball-milled once to make the ingredients uniformly mixed, and deionized water and ball-milling medium were added in a mass ratio of 1:2:5, and the mixture was ball-milled for 4 hours at a speed of 300 rpm in a planetary ball mill. After ball-milling, the obtained powder was dried at 120°C; The dried powder was passed through a 40-mesh sieve, sieved, placed in a crucible, compacted, and pre-sintered at a heating rate of 3°C / min to 880°C, kept at that temperature for 4 hours, and cooled in the furnace to obtain LiBa3Nb3Ti5O 21 Pre-burned material.

Citation Information

Patent Citations

  • Low-temperature melt Ba*Ti*Nb*O* microwave dielectric ceramic material and method for producing the same

    CN101172858A

  • Low-temperature sintered LTCC microwave dielectric ceramics material and preparation method thereof

    CN101224977A